The Prognostic Implication of Left Atrial Strain Parameters with Conventional Left Atrial Parameters for the Prediction of Adverse Outcomes in Asian Patients with Hypertrophic Cardiomyopathy—An Echocardiographic Study - Andre Seah; Tony Y. W. Li; Novi Yanti Sari; Chi-Hang Lee; Tiong-Cheng Yeo; James W. L. Yip; Yoke Ching Lim; Kian-Keong Poh; William K. F. Kong; Weiqin Lin; Ching-Hui Sia; Raymond C. C. Wong (Journal of Cardiovascular Development and Disease, 2025)
Background/Objectives: Left atrial function can be a tool for risk stratification for hypertrophic cardiomyopathy (HCM). Over the past decade, there has been growing interest in the application of strain analysis for earlier and more accurate prediction of cardiovascular disease prognosis. This study aimed to investigate the performance of left atrial strain analysis compared to conventional left atrial measures in predicting clinical outcomes in Asian patients with HCM. Methods and Results: This was a retrospective study involving 291 patients diagnosed with HCM between 2010 and 2017. Left atrial volumes were assessed using the method of discs in orthogonal plans at both end diastole and end systole. Left atrial (LA) strain was obtained using a post-hoc analysis with TOMTEC software. We tested the various left atrial parameters against outcomes of (1) heart failure hospitalization and (2) event-free survival from a composite of adverse events, including all-cause mortality, ventricular tachycardia (VT)/ventricular fibrillation (VF) events, appropriate device therapy if an implantable cardioverter defibrillator (ICD) was implanted, stroke, and heart failure hospitalization. The patients had a mean age of 59.0 ± 16.7 years with a male preponderance (71.2%). The cumulative event-free survival over a follow-up of 3.9 ± 2.7 years was 55.2% for patients with an abnormal LA strain versus 82.4% for patients without one (p < 0.001). Multivariable Cox regression analyses were performed separately for each LA parameter, adjusting for age, sex, LV mass index, LV ejection fraction (EF), E/e’, the presence of LV outflow tract (LVOT) obstruction at rest, and atrial fibrillation. An analysis showed that all parameters except for LAEF demonstrated an independent association with heart failure hospitalization. Left atrial strain outperformed the rest of the parameters by demonstrating an association with a composite of adverse events. Conclusions: In Asian patients with HCM, measures of left atrial strain were independently associated with heart failure hospitalization and a composite of adverse outcomes. Left atrial strain may be used as a tool to predict adverse outcomes in patients with HCM.